A Least-Square Model to Estimate Historical Percentages of Itinerant General Aviation Operations by Aircraft Types and Flight Rules at an Airport - Tao Li; Antonio A. Trani (Journal of Advanced Transportation)
Historical airport-level General Aviation (GA) activity plays an important role in airport managerial and operational decision-making processes. We developed a model to estimate historical percentages of itinerant GA operations by four aircraft types and two flight rules. The model is formulated as a least-square optimization model and can be applied to both towered and nontowered airports. We applied the model to airports in the Terminal Area Forecast and compared model estimates with the observed statistics. This study provides a method that could be used in the decision-making processes that require detailed historical GA operations.